590
reputation
2
14

Mats Granvik

Engineer.
$T(n,k)$ = https://oeis.org/A191898 $(n,k)$

$$\boxed{\Lambda(n)=\lim\limits_{s \rightarrow 1} \zeta(s)\sum\limits_{d|n} \frac{\mu(d)}{d^{(s-1)}}}$$ $$\sum\limits_{k=1}^{\infty}\sum\limits_{n=1}^{\infty} \frac{T(n,k)}{n^c \cdot k^s} = \sum\limits_{n=1}^{\infty} \frac{\lim\limits_{z \rightarrow s} \zeta(z)\sum\limits_{d|n} \frac{\mu(d)}{d^{(z-1)}}}{n^c} = \frac{\zeta(s) \cdot \zeta(c)}{\zeta(c + s - 1)}$$

$$1/a^{b+i c}=1/a^b (\cos (c \log (1/a))+i \sin (c \log (1/a)))$$

1/a^(b + I*c) = 1/a^b*(Cos[c*Log[1/a]] + I*Sin[c*Log[1/a]])

14,134725141734693790457251983562... = ?

https://oeis.org/A058303

s = ZetaZero[1];
Limit[Zeta[s*c]/Zeta[c + s - 1], c -> 1]
Limit[Zeta[s*c]/Zeta[c + s*c - 1], c -> 1]
Limit[(Zeta[s]*Zeta[c]/Zeta[c + s - 1] - Zeta[c]), c -> 1]

N[Table[2*Pi*Exp[1]*Exp[ProductLog[(n - 11/8)/Exp[1]]], {n, 1, 12}]]

Plot[RiemannSiegelTheta[t]/Pi + 
  Im[Log[Zeta[1/2 + I*t]] + I*Pi]/Pi, {t, 0, 60}, ImageSize -> Large]

Table[Limit[
  Zeta[s] Total[1/Divisors[n]^(s - 1)*MoebiusMu[Divisors[n]]], 
  s -> 1], {n, 1, 32}]

https://oeis.org/A177885

Table[Im[LogGamma[ZetaZero[n]/2]/Pi - 
   I*Im[ZetaZero[n]]/(2*Pi)*Log[Pi] + Log[Zeta[ZetaZero[n]]]/Pi + 
   I], {n, 1, 12}]

Plot[Im[LogGamma[1/4 + I*t/2]/Pi - I*t/(2*Pi)*Log[Pi] + 
   Log[Zeta[1/2 + I*t]]/Pi + I], {t, 0, 60}, ImageSize -> Large]

From this answer: http://math.stackexchange.com/a/442686/8530

by Raymond Manzoni.

=IF(OR(ROW()=1; COLUMN()=1);0; IF(ROW()>=COLUMN();EXP(-(1-11/8/(COLUMN()-1))/EXP(1)*SUM(INDIRECT(ADDRESS(ROW()-COLUMN()+1; COLUMN(); 4)&":"&ADDRESS(ROW()-1; COLUMN(); 4); 4)));0))

divided with: /2/PI()/EXP(1) gives reciprocal.

von Mangoldt function matrix:

=IF(OR(ROW()=1, COLUMN()=1), 1, IF(ROW()>=COLUMN(),-SUM(INDIRECT(ADDRESS(ROW()-COLUMN()+1,COLUMN(), 4)&":"&ADDRESS(ROW()-1, COLUMN(), 4), 4)),-SUM(INDIRECT(ADDRESS(COLUMN()-ROW()+1,ROW(), 4)&":"&ADDRESS(COLUMN()-1, ROW(), 4), 4))))

http://pastebin.com/u/MatsGranvik

Divisibility:

=IF(OR(COLUMN()=1); 1; IF(ROW()>=COLUMN();SUM(INDIRECT(ADDRESS(ROW()-COLUMN()+1;COLUMN()-1; 4)&":"&ADDRESS(ROW()-1; COLUMN()-1; 4); 4))-SUM(INDIRECT(ADDRESS(ROW()-COLUMN()+1;COLUMN(); 4)&":"&ADDRESS(ROW()-1; COLUMN(); 4); 4));0))

Clear[nn];

nn = 12

f[n_, s_] = ((s + 1)^(n - 1) + s - 1)/s;

TableForm[
 FullSimplify[
  Table[Integrate[Integrate[f[n, s], {n, 1, 2}], {s, 0, k}], {k, 0, 
    nn}]]]

Table[Limit[f[n, s], s -> 0], {n, 1, nn}]

Table[Limit[D[f[n, s], s], s -> 0], {n, 1, nn}]

Table[Limit[Integrate[f[-n, s], s], s -> 0], {n, 1, nn}]

FullSimplify[
 Differences[Table[Limit[Sum[f[-n, s], s], s -> 0], {n, -1, nn}]]]

Table[Limit[(-1 + n s (1 + s) + (2 + s)^n)/((1 + s)^2), s -> -1], {n, 1, nn}]

z = Integrate[((s + 1)^(-n - 1) + s - 1)/s, s];
a = Limit[z, s -> 0]
8
answers
18
questions
~6k
people reached

Top tags (30)

Score 4
Posts 7
Posts % 27
Score 3
Posts 3
Score 3
Posts 3
Score 2
Posts 3
Score 2
Posts 2
Score 1
Posts 2

Top posts (26) All Questions Answers | Votes Newest

View all questions and answers

Badges (16)

Gold

Silver

2

Rarest

Bronze

14

Rarest